Tailoring support to the female athlete: a cross-sectional online survey to observe current practices in high performance sport - Carmichael, M.; Roberts, A.; Perry, K.; Clarke, A. (International Journal of Sports Science & Coaching, 2025)
This study primarily aims to establish current practices to tailor support for female athletes, including menstrual cycle tracking, health screening, female-specific education, and other practical supports to address concerns related to menstruation. A secondary aim was to explore the relationships between the participant characteristics and practices implemented to tailor support for female athletes. One hundred and forty-one practitioners (i.e., coaches, athletic trainers, high performance managers) working with female athletes responded to an online survey between March and December 2023. Frequency analyses demonstrated that it is more common for practitioners to avoid discussing menstrual cycle tracking with athletes than to either encourage or require them to undertake tracking. Tracking was most often undertaken to establish and identify changes to athletes` usual menstrual characteristics, and to identify and manage menstrual symptoms. In terms of health screening, disordered eating and iron deficiency were screened for most commonly, while screening for pelvic floor dysfunction was least common. Female-specific nutrition, relative energy deficiency, and menstrual cycles were the topics most commonly included in female athlete-specific education targeted at athletes and practitioners. Further analysis revealed that respondents` tracking and education practices were closely associated. This study provides a snapshot into the practices that are currently implemented to tailor support to female athletes around their menstrual cycle.